The Influence of Price Perception, Sales Promotion, and Brand Image on Customer Satisfaction at UD Rizky Jaya B - Dwi Bagus Ramadhani; Nurul Badriyah; Titin Titin (Sean Institute, 2025)
This study aims to determine the Influence of Price Perception, Sales Promotion, and Brand Image on Customer Satisfaction at UD Rizky Jaya B both partially and simultaneously. The data collection technique used in this study is the purposive sampling technique. A person's purchasing behavior can be said to be something unique, because everyone's preferences and attitudes towards objects are different. In addition, consumers come from several segments, so what is wanted and needed is also different. The research method used is a quantitative method with an analysis tool using SPSS 22. The results of this study show that Price Perception (XI), Sales Promotion (X2), and Brand Image (X3) have a significant effect partially on Customer Satisfaction (Y) at UD Rizky Jaya B.